Quantifying physical demands in the National Basketball Association - Challenges around developing best-practice models for athlete care and performance - McLean, B. D.; Strack, D.; Russell, J.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2019)
The National Basketball Association (NBA) has an extremely demanding competition schedule, requiring its athletes to compete in 82 regular-season games over a 6-mo period (~3.4 games/wk). Despite the demanding schedule and high value of athletes, there is little public information on the specific game and training demands required to compete in the NBA. Although provisions in the NBA collective-bargaining agreement allow for research designed to improve player health and broaden medical knowledge, such information is sparse in the available literature. In relation to the physical demands of the NBA, the current lack of information likely results from multiple factors including limited understanding of (basketball-related) emerging technologies, impact of specific league rules, and steps taken to protect players in the age of Big Data. This article explores current limitations in describing specific game/training demands in the NBA and provides perspectives on how some of these challenges may be overcome. The authors propose that future collaborations between league entities, NBA clubs, commercial partners, and outside research institutions will enhance understanding of the physical demands in the NBA (and other health- and performance-related areas). More detailed understanding of physical demands (games, practices, and travel) and other health-related areas can augment player-centered decision making, leading to enhanced player care, increased availability, and improved physical performance.